HUBUNGAN PENGETAHUAN DAN PRAKTIK PEMBERIAN MAKAN BAYI DAN ANAK (PMBA) SERTA PENGGUNAAN GARAM BERYODIUM DENGAN KEJADIAN STUNTING - Heri Gunawan; Siti Fatimah; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Stunting problems often arise as a result of a lack of knowledge and skills in meeting the nutritional needs of toddlers. Infant and Young Child Feeding (IYCF) is an effort aimed at increasing the knowledge and skills of the community to deal with nutritional problems independently. In addition to feeding patterns, adequate intake of iodine is required for normal physical growth during pregnancy and early life. This study aims to analyze the relationship between knowledge and practice of IYCF and consumption of iodized salt with the case of stunting in toddlers aged 12-24 months.This research is an analytic observational study using a cross sectional design. 87 samples were selected using random sampling technique. The data was collection on the level of knowledge and practice of PMBA carried out interviews with respondents using a questionnaire, collecting data on the use of iodized salt by testing for iodine levels using Lugol's solution (iodine test), measuring body length using an Infantometer and determining nutritional status processed with the WHO anthro application and analyzing data using the test. Continuity Correction stats. IYCF knowledge of the respondents at 76.0% is classified as good, IYCF practice of the respondents at 69% is classified as good and the use of Iodized Salt is at 35.6%. The Continuity Correction ”test showed that there was” a significant association between IYCF“knowledge (p=0.001; PR =14.9), IYCF practice (p=0.001; PR =10.6) and ”the use of iodized salt” (p=0.017; PR =3.7) and the incidence of stunting in children aged 12-24 months.There is an,.association between IYCF practice and knowledge and the use of iodized salt and ”the”incidence”” of stunting in ”children ”aged 12-24 months.